Implications of Student Loan and Finance Management Skills for Undergraduate Students - Diana Yankovich; Nirmaljit Rathee; Vikramjit S. Rathee (European Scientific Journal, ESJ, 2023)
As the Presidential elections in 2024 are approaching, public opinions and politicians’ statements about student loans are presented more often. To curb educational borrowing, the entire society is involved. Institutions of higher education are highly engaged in securing possible funds for scholarships and grants to provide their students with the best and most efficient education. States offer scholarships, and students are becoming more selective about their institution, study major, and lifestyle choices during their undergraduate studies.  Many borrowers lack a clear understanding of loan terms and finance management skills. This study was conducted to determine the money management skills of undergraduates, their perceived amount of educational loans anticipated upon graduation, and its impact on their academic performance. A specifically designed survey instrument was administered to a total of 565 participants who were students at one of the US HBCUs in the North-Eastern region of the United States. The results revealed significant race differences in the perceived expected amount of debt upon graduation. The study further indicates a heightened requirement for academic guidance for students whose undergraduate GPAs fall within the range of 2.00 to 3.00, aiming to enhance their retention until graduation within the present institution. Student athletes expressed a significantly higher financial self-efficacy than non-athletes.